Constructions of perfect Gaussian integer sequences of odd prime length - Yubo LI; Miao CHEN; Tao LIU; Ying ZHANG (Tongxin xuebao)
Constructions of perfect Gaussian integer sequences (PGIS) based on the cyclotomic classes were proposed.The PGIS with degree 3 and 5 were constructed respectively from the cyclotomic classes of order 2 and 4.The presented sequences with odd prime length have ideal autocorrelations.The methods solved the problem that the traditional constructions of PGIS from the cyclotomic classes have high computational complexity.As a result,this kind of sequences will be useful in the applications of wireless communications.